Increased detection of Plasmodium knowlesi in Sandakan division, Sabah as revealed by PlasmoNex - Xiang, Ting Goh; Yvonne Ai, Lian Lim; Indra, Vythilingam; Ching, Hoong Chew; Ping, Chin Lee; Romano, Ngui; Tian, Chye Tan; Nan, Jiun Yap; Veeranoot, Nissapatorn; Kek, Heng Chua (BioMed Central Ltd., 2013)
Background: Plasmodium knowlesi is a simian malaria parasite that is widespread in humans in Malaysian Borneo. However, little is known about the incidence and distribution of this parasite in the Sandakan division, Malaysian Borneo. Therefore, the aim of the present epidemiological study was to investigate the incidence and distribution of P. knowlesi as well as other Plasmodium species in this division based on a most recent developed hexaplex PCR system (PlasmoNex™). Methods: A total of 189 whole blood samples were collected from Telupid Health Clinic, Sabah, Malaysia, from 2008 to 2011. All patients who participated in the study were microscopically malaria positive before recruitment. Complete demographic details and haematological profiles were obtained from 85 patients (13 females and 72 males). Identification of Plasmodium species was conducted using PlasmoNex™ targeting the 18S ssu rRNA gene. Results: A total of 178 samples were positive for Plasmodium species by using PlasmoNex™. Plasmodium falciparum was identified in 68 samples (38.2%) followed by 64 cases (36.0%) of Plasmodium vivax, 42 (23.6%) cases of P. knowlesi, two (1.1%) cases of Plasmodium malariae and two (1.1%) mixed-species infections (i e, P. vivax/ P. falciparum). Thirty-five PlasmoNex™ positive P. knowlesi samples were misdiagnosed as P. malariae by microscopy. Plasmodium knowlesi was detected in all four districts of Sandakan division with the highest incidence in the Kinabatangan district. Thrombocytopaenia and anaemia showed to be the most frequent malaria-associated haematological complications in this study. Conclusions: The discovery of P. knowlesi in Sandakan division showed that prospective studies on the epidemiological risk factors and transmission dynamics of P. knowlesi in these areas are crucial in order to develop strategies for effective malaria control. The availability of advanced diagnostic tool PlasmoNex™ enhanced the accuracy and accelerated the speed in the diagnosis of malaria